Impact of Inversion Domain Boundaries on the Electronic Properties of 3C‐SiC. Issue 9 (16th June 2022) - Scalise, Emilio; Zimbone, Massimo; Marzegalli, Anna
Abstract : Inversion domain boundaries are extended defects affecting cubic silicon carbide (3C‐SiC) layers grown on the on‐axis (001) Si wafers. Their impact on the device performance is still debated and a clear connection to their electronic properties at the atomistic scale is still missing. By comparing the first‐principles atomistic models and scanning transmission electron microscopy imaging, the most relevant structures of inversion domain boundaries laying both in the {110} and {111} planes are identified. Their calculated electronic structures shed light on the relevance that these extended defects may have in the degradation of the performances of the 3C‐SiC devices. Abstract : First‐principles atomistic models and scanning transmission electron microscopy imaging are used to identify the most relevant structures of inversion domain boundaries laying both in the {110} and {111} planes. Their calculated electronic structures suggest a moderate impact that these extended defects may have on the performances of the cubic silicon carbide (3C‐SiC) devices.